2015
DOI: 10.1097/prs.0000000000001114
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Crushed Cartilage and Fibrin Sealant for Radix Augmentation in Asian Rhinoplasty

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…5 The authors suggested placing cartilage dices on the radix and then covering the dices with fibrin glue. This concept deviates in several ways from the diced cartilage glue graft described previously, 3,4 prompting us to highlight the key steps we consider to be crucial for an optimal anatomic shape of the graft and its long-term success ( Figure).…”
Section: Surgical Techniquementioning
confidence: 99%
“…5 The authors suggested placing cartilage dices on the radix and then covering the dices with fibrin glue. This concept deviates in several ways from the diced cartilage glue graft described previously, 3,4 prompting us to highlight the key steps we consider to be crucial for an optimal anatomic shape of the graft and its long-term success ( Figure).…”
Section: Surgical Techniquementioning
confidence: 99%
“…Yu et al 9 conducted a study of radix augmentation using crushed cartilage with fibrin sealant in Asian rhinoplasty; they reported that this technique was reliable and suitable for radix augmentation, with a reasonable complication rate. 9 In some cases, we used crushed cartilage wrapped in fascial lata, which showed good outcomes and acceptable results, with a low rate of complications (5 of 79 patients required revision corrective surgery). Crushed cartilage grafts are applied to cover anomalies and generate a softer nose, and they can also be applied to augment the radix.…”
Section: Discussionmentioning
confidence: 99%
“…The interrater and intrarater reliabilities were assessed using intraclass coefficient. Intra-class coefficients between 0.60 and 0.80 were considered substantial; coefficients greater than 0.80 were excellent [ 6 ].…”
Section: Methodsmentioning
confidence: 99%